Kant-Studien : Philosophische Zeitschrift der Kant-Gesellschaft (De Gruyter, 1897)
Kant-Studien is devoted to philosophical and historical studies on Kant and Kantian topics. The journal publishes a comprehensive bibliography of new works on Kant, and provides reviews of the most important books. It is thus the leading German and English language resource on the current state of Kant research.